TINJAUAN YURIDIS TERHADAP KEWAJIBAN VERIFIKASI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) ATAS PERALIHAN HAK ATAS TANAH DAN BANGUNAN DI KOTA PEKANBARU - ERIKA JENRI HALASAN PANJAITAN (PREMISE LAW JURNAL, 2015)
Since the enactment of Law No.28/2009 on Local Taxes and Levies has resulted in the problem in the implementation of collecting the duty obtained from the Right to Land and Building in the city of Pekanbaru. The problem occured because the City Mayor of Pekanbaru established the Local Regulation No.10/2011 on the System and Procedure of Collecting the Duty Obtained from the Right to Land and Building by doing the verification before signing the deed on the transfer of right to land and building before the Land Certificate Issuing Officer/Notary. Law No.28/2009 on Local Taxes and Levies or the Government Regulation No.91/2010 on Kinds of Local Taxes Collected Based on the Determination of Head of Region or Paid by the Taxpayer Himself has regulated that the collection of tax of the duty obtained from the Right to Land and Building should be done through Self Assesment System and does not regulation verification. Keywords: Verification, Duty Obtained from the Right to Land and Building, City of Pekanbaru